miR-874: An Important Regulator in Human Diseases - Zhang, Qiudan; Zhong, Chenming; Yan, Qianqian; Zeng, Ling-hui; Gao, Wei; Duan, Shiwei (Frontiers in Cell and Developmental Biology, 2022)
miR-874 is located at 5q31.2, which is frequently deleted in cancer. miR-874 is downregulated in 22 types of cancers and aberrantly expressed in 18 types of non-cancer diseases. The dysfunction of miR-874 is not only closely related to the diagnosis and prognosis of tumor patients but also plays an important role in the efficacy of tumor chemotherapy drugs. miR-874 participates in the ceRNA network of many long non-coding RNAs or circular RNAs, which is closely related to the occurrence and development of cancer and other non-cancer diseases. In addition, miR-874 is also involved in the regulation of multiple signaling pathways, including the Wnt/β-catenin pathway, the Hippo pathway, the PI3K/AKT pathway, the JAK/STAT pathway, and the Hedgehog signaling pathway. This review summarizes the key molecular functions of miR-874 in the biological processes of tumor cell survival, apoptosis, differentiation, and tumorigenesis, and reveal the value of miR-874 as a cancer biomarker in tumor diagnosis and prognosis. Future work is necessary to explore the potential clinical application of miR-874 in chemotherapy resistance.